ANALISIS PENGARUH CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN DENGAN FIRM SIZE SEBAGAI VARIABEL KONTROL (Studi Empiris : Perusahaan Go Public Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2009 sampai dengan 2014) - Hardiyawan, Aditya Tri; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2015)
This  Research  aims  to  analyze  the  influence  of  board  independent,  board    ofdirectors, institusional ownership, managerial ownership, and leverage to financial performance that measured by ROA. fThis research also used firm size as control variable. Case study on company non financial in Indonesian Stock Exchange in period 2009-2014.The sampling technique used in this research is purposive sampling. There are 60 companies that used during the research. Analytical technique used in this research is multiple regression analysis by using SPSS 21. In this study the data were obtained from the Indonesian Capital Market Directory (ICMD) 2009-2014, IDX Company Report 2009-2014, and www.idx.co.id. Analysis technique used Ordinary Least Square Regressio (OLS), statistical t-test and classic assumption test that includes a test of normality test, multicollinearity test, heteroskedastisitas test, autucorrelation test.The result shows that board independent and managerial ownership haven’t influenced to ROA, board of directors and institutional ownership has positive influenced to ROA,  and leverage has negative influenced to ROA,